Photon-Working Switches - Yokoyama, Yasushi; Nakatani, Keitaro (Springer Japan : Imprint: Springer, 2017)
This book focuses on photoswitches. The objective of the book is to introduce researchers and graduate course students who are interested in "photon-working switches" not only to the fundamentals but also to the latest research being carried out in this field. Light can reach a target substrate without any physical contact to deliver energy. The energy can induce changes in the structure of the molecules included in the substrate so that its properties and functions are made switchable by light irradiation. When a substrate is able to revert to its original state, this system can be regarded as a "photon-working switch". The terms "photon-working switches" or "photoswitches" are almost equivalent in meaning to "photochromism"; however, they focus on the "switching of functions" of chemical species rather than their "reversible transformation". Most of the authors of this volume are members of PHENICS, an international research group on organic molecular photoswitches composed of research institutions from France, Japan, Russia, China and Germany. Since its inception in 2008, PHENICS has promoted active research to develop the field. This book commemorates the group's eighth year of collaborative research.